Novel porous carbon material and preparation method thereof

By mixing and carbonizing needle coke and high-volatile coal tar pitch, a porous carbon material was prepared, which solved the problems of pore collapse and low strength, realized the preparation of silicon carbide-carbon composite materials with high residual carbon content, and improved the performance of the material under dry friction conditions.

CN120736899APending Publication Date: 2025-10-03SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510832097.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing methods for preparing porous carbon materials have problems such as pore collapse, low strength and complex preparation process, making it difficult to meet the service performance requirements of silicon carbide-carbon composite materials under dry friction conditions.

Method used

Using needle coke and high-volatile coal tar pitch as raw materials, through mixing, crushing, dry pressing and carbonization treatment, the microstructure of porous carbon is controlled to form a rich pore structure, avoiding bulging or cracking of the sample, and realizing the preparation of silicon carbide-carbon composite materials with high residual carbon content.

Benefits of technology

The simple and efficient preparation of porous carbon materials has been achieved. By regulating the porous carbon microstructure and controlling the degree of reaction between molten silicon and carbon, the performance of silicon carbide-carbon composite materials has been improved and the bonding strength between the two has been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120736899A_ABST
    Figure CN120736899A_ABST
Patent Text Reader

Abstract

The invention relates to a novel porous carbon material and a preparation method thereof. The preparation method of the novel porous carbon material comprises the following steps: (1) heating, stirring and mixing needle coke and coal tar pitch with a certain softening point in a kneading machine to obtain mixed particles in which the needle coke is wrapped by molten pitch; (2) crushing and screening the mixed particles obtained in the step (1) into mixed powder with a certain particle size, carrying out dry pressing molding, and heating in a drying oven to melt and solidify the asphalt again to obtain a porous carbon blank; and (3) carbonizing the porous carbon blank obtained in the step (2) to obtain the novel porous carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous carbon materials and relates to a novel porous carbon material and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics have excellent physical and chemical properties such as high hardness, high rigidity, high thermal conductivity, high temperature resistance, corrosion resistance, neutron irradiation resistance, and wear resistance. They are widely used in heat exchange components, precision bearings, and the semiconductor industry. Due to the excellent performance of silicon carbide, it has gradually become a favorable candidate material for sealing in my country's aerospace and nuclear power fields in recent years. However, silicon carbide has problems with high wear rate and large friction coefficient under dry friction conditions, which makes it easy to fail due to wear under dry friction conditions, resulting in huge losses. In order to improve the service performance of silicon carbide materials under dry friction and complex working conditions, a silicon carbide-carbon self-lubricating composite material with silicon carbide as the base can be prepared by introducing carbon material as a second-phase lubricating material.

[0003] Reaction sintering is currently one of the most commonly used methods for preparing silicon carbide-carbon composites. It is formed by infiltrating molten silicon into a porous carbon precursor to react with carbon. The silicon carbide generated in situ by molten silicon and carbon during the reaction can enhance the bonding strength between carbon and silicon carbide. At the same time, since the carbon material has a layered crystal structure, its dry friction performance can be improved.

[0004] Currently, the commonly used methods for preparing porous carbon materials include activation, template, and sol-gel methods. The activation method is prone to pore collapse, while the template method is relatively complex. The sol-gel method, with its relatively simple preparation process, often produces porous carbon precursors with low strength and prone to pore collapse. Therefore, a new method for preparing porous carbon materials is urgently needed. Summary of the Invention

[0005] To address the challenges of existing reactive sintering methods for preparing silicon carbide-carbon composites, the present invention provides a novel porous carbon material and a method for preparing the same. The porous carbon material serves as a porous carbon precursor for reactive sintering to prepare silicon carbide-carbon composites. The method provides a simple process and can adjust the degree of reaction between molten silicon and carbon by controlling the microstructure of the porous carbon, thereby producing a silicon carbide-carbon composite with a high residual carbon content.

[0006] In a first aspect, the present invention provides a method for preparing a novel porous carbon material, comprising the following steps: (1) placing needle coke and coal tar pitch having a certain softening point in a kneader, heating and stirring the mixture to obtain mixed particles in which the needle coke is coated with molten pitch; (2) crushing and screening the mixed particles obtained in step (1) into a mixed powder of a certain particle size, dry-pressing the mixed powder, and heating the mixed powder in an oven to re-melt and solidify the asphalt to obtain a porous carbon blank; (3) Carbonizing the porous carbon blank obtained in step (2) to obtain the novel porous carbon material.

[0007] Preferably, in step (1), the particle size of the needle coke is 15 to 150 μm; The softening point of the coal tar pitch is 45-180°C, preferably 80-115°C; the volatile matter of the coal tar pitch is ≥50%, preferably 60-75%; Preferably, the mass ratio of the needle coke to coal tar pitch is (1-4):1, preferably (1.5-3):1.

[0008] Preferably, in step (1), the mixing method is: first pour the needle coke into a kneader, heat and stir for 30 to 60 minutes, and then add the molten asphalt into the kneader for kneading; wherein the heating and stirring temperature is 150 to 250°C, preferably 170 to 220°C; the kneading time after adding the molten asphalt is 1 to 3 hours, preferably 1.5 to 2 hours.

[0009] Preferably, in step (2), the particle size of the mixed powder after crushing and screening is ≤250 μm, preferably 100 to 250 μm.

[0010] Preferably, in step (2), the dry pressing pressure is 0 to 18 MPa, preferably 8 to 18 MPa.

[0011] Preferably, in step (2), the heating temperature is 150-250° C., and the heating time is 0.5-3 h; preferably, the heating temperature is 190-220° C., and the heating time is 1-2 h.

[0012] Preferably, in step (3), the parameters of the carbonization treatment include: evacuating to below 10 Pa, heating to 450-600°C at a heating rate of 1-3°C / min and keeping warm for 0-8h, then heating to 900-1000°C at a heating rate of 1-3°C / min and keeping warm for 0.5-2h, then introducing high-purity argon gas and cooling to room temperature with the furnace.

[0013] In a second aspect, the present invention provides a novel porous carbon material prepared according to the above preparation method.

[0014] Preferably, the open porosity of the novel porous carbon material is 28-53%, and the bulk density is 0.884-1.354 g / cm 3 .

[0015] In the present invention, high-volatile asphalt is used as a binder, and the volatile substances generated during the carbonization process, such as a large amount of sulfur oxides, nitrogen oxides, volatile organic compounds, etc., can form a rich pore structure in the green body. At the same time, since a large amount of volatile substances will be generated during the carbonization process of the asphalt, the sample directly dry-pressed under a higher pressure will not be able to fully escape the gas during the carbonization process due to the dense structure of the green body, and the sample will have problems such as bulging and deformation. However, it is impossible to directly dry-press the sample under a lower pressure. Therefore, in the present invention, after dry-pressing at a lower pressure, the metal mold is directly placed in an oven for heating, so that the asphalt is melted and solidified again. At this time, a complete porous carbon green body can be obtained, and because the molding pressure is low, the porous carbon green body obtained has a loose structure, so that the volatile substances generated during the carbonization process can escape smoothly. According to the thermogravimetric curve, it can be seen that the mass loss of asphalt is most serious at around 450°C during the carbonization process. Therefore, long-term heat preservation at 450°C, the intermediate phase transition temperature of coal tar during carbonization, is also conducive to the full volatilization of volatile substances. At the same time, due to the loose structure of the porous carbon blank, sample damage caused by bulging or cracking of the porous carbon blank during the carbonization process is also avoided.

[0016] Beneficial effects: (1) The present invention provides a method for preparing a novel porous carbon material. The porous carbon material is used as a porous carbon precursor for reactive sintering to prepare a silicon carbide-carbon composite material. The porous carbon microstructure can be controlled by adjusting the porous carbon preparation process parameters, such as particle size, molding pressure, holding time and other conditions. Thus, when applied to reactive sintering, the degree of reaction between molten silicon and carbon can be controlled, thereby realizing the preparation of a silicon carbide-carbon composite material with a high residual carbon content. (2) The preparation method of the porous carbon material provided by the present invention has a simpler preparation process compared to existing porous carbon preparation methods such as template method, activation method, and sol-gel method. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The TGA and DSC curves of the porous carbon blank of the present invention are shown below: Figure 2 This is a surface morphology of the porous carbon material prepared in Example 4 of the present invention; Figure 3 The pore size distribution diagram of the porous carbon materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1-2 of the present invention; Figure 4 The pore size distribution diagram of the porous carbon materials prepared in Examples 3-4 and Comparative Example 3 of the present invention; Figure 5 This is a BSE image of a composite material prepared by sintering the porous carbon material obtained in Example 4 of the present invention; Figure 6The sample is prepared by sintering the porous carbon material obtained in Comparative Example 1 of the present invention; Figure 7 This is a BSE image of a composite material prepared by reactive sintering the porous carbon material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0018] To further illustrate the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be noted that the modification method of the design of the present invention is not limited to these specific embodiments. Without departing from the spirit and connotation of the design of the present invention, equivalent replacements and modifications made by those skilled in the art based on the content of the present invention are also within the scope of the present invention.

[0019] In the present invention, needle coke is used as the aggregate and high-volatile asphalt is used as the binder. The materials are mixed, crushed, screened, dry-pressed, and heated to produce a porous carbon blank. This is then carbonized to create a novel porous carbon material. The use of high-volatile asphalt as the binder allows for a large amount of gas to escape during the carbonization process, forming a rich pore structure within the blank. Simultaneously, after preforming under low pressure, the asphalt is heated in an oven to re-melt and solidify, resulting in a porous carbon blank with a loose structure. Furthermore, the carbonization process is conducted at the intermediate phase transition temperature of the coal tar pitch for a long period of time, which facilitates the full volatilization of volatile substances during the carbonization process, thereby forming a rich pore structure within the blank.

[0020] In the present invention, high-volatility asphalt is used as a binder, and the volatile substances generated during the carbonization process, such as a large amount of sulfur oxides, nitrogen oxides, volatile organic compounds, etc., can form a rich pore structure in the green body. However, since a large amount of volatile substances will be generated during the carbonization process of the asphalt, the sample directly dry-pressed under a higher pressure will not be able to fully escape due to the dense structure of the green body. The sample will have problems such as bulging and deformation. However, the mixed powder cannot be directly dry-pressed under a lower pressure. Therefore, in the present invention, after dry-pressing at a lower pressure, the metal mold is directly placed in an oven for heating, so that the asphalt is melted and solidified again. At this time, a complete porous carbon green body can be obtained. Moreover, due to the low molding pressure, the porous carbon green body obtained has a loose structure, so that the volatile substances generated during the carbonization process can escape smoothly. According to the thermogravimetric curve, the mass loss of pitch during carbonization is most severe at around 450°C. Therefore, holding the carbonization temperature at 450°C, the intermediate phase transition temperature of coal tar, for a long time is also conducive to the full volatilization of volatile substances. Moreover, due to the loose structure of the porous carbon blank, it also avoids sample damage caused by bulging or cracking of the porous carbon blank during carbonization. During the preparation of porous carbon materials, the higher the volatile content of coal tar pitch, the greater the porosity of the porous carbon material. With the increase of molding pressure, the porosity of porous carbon decreases monotonically, and the pore size gradually decreases to a certain extent and then remains stable. With the increase of particle size, the pore size of porous carbon gradually increases. Prolonging the holding time at 450°C will increase the porosity of porous carbon materials.

[0021] The following is an exemplary description of the preparation method of the novel porous carbon material provided by the present invention.

[0022] Needle coke is used as aggregate and coal tar pitch is used as binder, and the two are placed in a kneader and mixed evenly to obtain mixed particles coated with pitch.

[0023] In an optional embodiment, the particle size of the needle coke is 15 to 150 μm. The softening point of the coal tar pitch is 45 to 180°C, preferably 80 to 115°C; the volatile matter of the coal tar pitch is ≥50%, preferably 60 to 75%. If the volatile matter of the coal tar pitch is too low, the formed blank will produce less volatile substances during the carbonization process, and the prepared carbon material structure will be denser. The mass ratio of the needle coke to coal tar pitch is (1 to 4):1, preferably (1.5 to 3):1.

[0024] In an optional embodiment, the mixing method is: first pour the needle coke into a kneader, turn on the heating and stirring device, heat and stir for 30 to 60 minutes, and then add the molten asphalt into the kneader for kneading; wherein the heating and stirring temperature is 150 to 250°C, preferably 170 to 220°C; the kneading time after adding the molten asphalt is 1 to 3 hours, preferably 1.5 to 2 hours.

[0025] The obtained mixed particles are crushed and sieved, the sieved powder is put into a mold for dry pressing and then placed in an oven for heating, and the sample is taken out after cooling to obtain a porous carbon blank.

[0026] In an optional embodiment, the particle size of the mixed powder after crushing and screening is ≤250 μm, preferably 100-250 μm. If the particle size of the mixed powder after crushing and screening is too small, the pore size of the prepared porous carbon material will be too small, which will hinder the penetration of silicon during the subsequent reaction and sintering process, and cannot meet the requirements for preparing silicon carbide-carbon composite materials.

[0027] In an optional embodiment, the dry pressing pressure is 0 to 18 MPa, preferably 8 to 18 MPa. Excessive dry pressing pressure may result in a low porosity of the porous carbon material, which may hinder the penetration of silicon during the subsequent reaction sintering process and fail to meet the requirements for preparing silicon carbide-carbon composite materials.

[0028] In an optional embodiment, the heating temperature is 150-250° C., and the heating time is 0.5-3 h; preferably, the heating temperature is 190-220° C., and the heating time is 1-2 h.

[0029] The porous carbon blank is placed in a graphite crucible, and the graphite crucible is placed in a high-temperature reaction furnace for carbonization treatment to obtain the novel porous carbon material.

[0030] In an optional embodiment, the carbonization treatment parameters include: evacuating to below 10 Pa, heating to 450-600°C at a heating rate of 1-3°C / min and holding for 0-8 hours, then heating to 900-1000°C at a heating rate of 1-3°C / min and holding for 0.5-2 hours, followed by the introduction of high-purity argon gas and furnace cooling to room temperature. Thermogravimetric curves indicate that coal tar pitch experiences significant mass loss at around 450°C, the intermediate phase transition temperature, generating volatile substances such as large amounts of sulfur oxides, nitrogen oxides, and volatile organic compounds. The purpose of maintaining the temperature at the intermediate phase transition temperature for a long time is to allow the volatile substances to fully escape, thereby forming a porous structure.

[0031] In the present invention, the open porosity of the novel porous carbon material measured by the Archimedean drainage method is 28-53%, and the bulk density is 0.884-1.354 g / cm 3 The pore size of the novel porous carbon material increases with the increase of particle size and decreases with the increase of molding pressure, but begins to remain stable after decreasing to a certain extent.

[0032] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description herein, and are not limited to the specific numerical values ​​exemplified below.

[0033] Example 1

[0034] This embodiment 1 provides a method for preparing a novel porous carbon material, comprising the following steps: (1) Weigh 280 g of green needle coke with a particle size of 100 to 150 μm and 120 g of coal tar pitch with a softening point of 115° C. and a volatile matter content of 66% for later use; (2) Pour the needle coke into a kneader, turn on the heating and stirring device, control the motor frequency to 30 Hz, the stirring temperature to 190°C, heat and stir for 30 minutes, and heat the asphalt to a molten state. Then add the molten coal tar pitch into the kneader and mix it with the needle coke. After adding the molten asphalt, the kneading time is 1.5 hours. After the kneading is completed, remove the mixed particles while they are still hot and cool them to room temperature. (3) crushing the mixed particles obtained in step (2) using a mechanical crusher, and then sieving to obtain a mixed powder with a particle size between 150 and 200 μm; (4) The mixed powder obtained in step (3) is placed in a metal mold and formed under a pressure of 0 MPa (i.e., dry pressing is not performed), and the metal mold containing the sample is placed in a 200°C oven and heated for 1.5 hours. After cooling, the sample is demolded and taken out to obtain a porous carbon blank; (5) The porous carbon blank obtained in step (4) is placed in a graphite crucible, and the graphite crucible is placed in a high-temperature reactor. The high-temperature reactor is evacuated to below 10 Pa, and the temperature is increased to 450°C at a heating rate of 1°C / min and kept warm for 8 hours. The temperature is then increased to 1000°C at a heating rate of 1°C / min and kept warm for 2 hours. Subsequently, high-purity argon gas is introduced and the furnace is cooled to room temperature. The sample is taken out to obtain a porous carbon material.

[0035] The open porosity of the porous carbon material obtained in Example 1 was measured by the Archimedean drainage method to be 49.29%, and the bulk density was 0.946 g / cm 3 The mercury intrusion test showed that the pore sizes of the porous carbon materials are mainly concentrated at 1.77 μm, 21.6 μm and 27.69 μm.

[0036] Example 2

[0037] The preparation process of the porous carbon material in this Example 2 refers to that in Example 1, with the only difference being that in step (3), the particle size of the mixed particles obtained by screening is 200-250 μm.

[0038] The microstructure of Example 2 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 2 was measured by the Archimedean drainage method to be 46.20%, and the bulk density was 0.937 g / cm 3 The mercury intrusion test showed that the pore sizes of the porous carbon materials were mainly concentrated at 1.91 μm, 32.05 μm and 39.33 μm.

[0039] Example 3

[0040] The preparation process of the porous carbon material in this Example 3 refers to that in Example 1, with the only difference being that in step (4), the molding pressure is 8 MPa.

[0041] The microstructure of Example 3 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 3 was measured by the Archimedean drainage method to be 40.06%, and the bulk density was 1.123 g / cm 3 The mercury intrusion test showed that the pore sizes of the porous carbon materials were mainly concentrated at 1.72 μm and 12.14 μm.

[0042] Example 4

[0043] The preparation process of the porous carbon material in this Example 4 refers to that in Example 1, with the only difference being that in step (4), the molding pressure is 10 MPa. The porous carbon material prepared in this Example 4 is used as a precursor to prepare a silicon carbide-carbon composite material, comprising the following steps: placing the porous carbon precursor into a graphite crucible coated with boron nitride, weighing a certain amount of elemental silicon particles and covering the porous carbon precursor, then placing the graphite crucible into a vacuum sintering furnace, evacuating to below 10 Pa, heating to 1550° C. and holding for 0.5 h, then introducing high-purity argon gas and cooling to room temperature with the furnace to obtain a silicon carbide-carbon composite material.

[0044] The microstructure of Example 4 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 4 was measured by the Archimedean drainage method to be 37.35%, and the bulk density was 1.176 g / cm 3 The mercury intrusion test showed that the pore sizes of the porous carbon precursor were mainly concentrated at 1.61 μm and 11.86 μm.

[0045] Example 5

[0046] The preparation process of the porous carbon material in this Example 5 refers to that in Example 1, with the only difference being that in step (3), the particle size of the mixed particles obtained by screening is 100-150 μm; and in step (4), the molding pressure is 5 MPa.

[0047] The microstructure of Example 5 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 5 was measured by the Archimedean drainage method to be 38.46%, and the bulk density was 1.112 g / cm 3 .

[0048] Example 6

[0049] The preparation process of the porous carbon material in this Example 6 refers to that in Example 5, with the only difference being that in step (1), 320 g of needle coke with a particle size of 100 to 150 μm and 80 g of coal tar pitch with a softening point of 115° C. and a volatile matter of 66% are weighed.

[0050] The microstructure of Example 6 is similar to that of Example 5. The open porosity of the porous carbon material obtained in Example 6 was measured by the Archimedean drainage method to be 36.86%, and the bulk density was 1.198 g / cm 3 .

[0051] Example 7

[0052] The preparation process of the porous carbon material in this Example 7 refers to that in Example 5, with the only difference being that in step (1), 200 g of needle coke with a particle size of 100 to 150 μm and 200 g of coal tar pitch with a softening point of 115° C. and a volatile matter of 66% are weighed.

[0053] The microstructure of Example 7 is similar to that of Example 5. The open porosity of the porous carbon material obtained in Example 7 was measured by the Archimedean drainage method to be 41.10%, and the bulk density was 1.101 g / cm 3 .

[0054] Example 8

[0055] The preparation process of the porous carbon material in this Example 8 refers to that in Example 4, with the only difference being that in step (1), 280 g of needle coke with a particle size of 15 μm and 120 g of coal tar pitch with a softening point of 115° C. and a volatile matter of 66% are weighed.

[0056] The open porosity of the porous carbon material obtained in Example 8 was measured by the Archimedean drainage method to be 44.92%, and the bulk density was 1.140 g / cm 3 .

[0057] Example 9

[0058] The preparation process of the porous carbon material in this Example 9 refers to that in Example 3, with the only difference being that in step (5), the temperature is raised to 200°C at 3°C / min, then raised to 450°C at 1°C / min and kept at this temperature for 0 h (i.e., no heat preservation is performed), and finally raised to 1000°C at 3°C / min and kept at this temperature for 0.5 h.

[0059] The microstructure of Example 9 is similar to that of Example 3. The open porosity of the porous carbon material obtained in Example 9 was measured by the Archimedean drainage method to be 37.04%, and the bulk density was 1.139 g / cm 3 .

[0060] Example 10

[0061] The preparation process of the porous carbon material in this Example 10 refers to that in Example 1, with the only difference being that: in step (1), 280 g of needle coke with a particle size of 100 to 150 μm and 120 g of coal tar pitch with a softening point of 45°C and a volatile matter of 79% are weighed; in step (2), the kneading temperature is 170°C and the kneading time is 1 h (the kneading time is the kneading time after the addition of molten pitch); in step (4), the oven heating temperature is 150°C and the heating time is 0.5 h.

[0062] The microstructure of Example 10 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 10 was measured by the Archimedean drainage method to be 52.67%, and the bulk density was 0.890 g / cm 3 .

[0063] Example 11

[0064] The preparation process of the porous carbon material in this Example 11 refers to that in Example 1, with the only difference being that: in step (1), 280 g of needle coke with a particle size of 100 to 150 μm and 120 g of coal tar pitch with a softening point of 180°C and a volatile matter of 52% are weighed; in step (2), the kneading temperature is 220°C and the kneading time is 3 h; in step (4), the oven heating temperature is 250°C and the heating time is 3 h.

[0065] The microstructure of Example 11 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Example 11 was measured by the Archimedean drainage method to be 44.25%, and the bulk density was 1.048 g / cm 3 .

[0066] Comparative Example 1

[0067] The preparation process of the porous carbon material in this comparative example 1 refers to that in Example 1, with the only difference being that in step (3), the particle size of the mixed particles obtained by screening is 0 to 100 μm. The porous carbon material prepared in this comparative example 1 is used as a precursor to prepare a silicon carbide-carbon composite material, comprising the following steps: placing the porous carbon precursor in a graphite crucible coated with boron nitride, weighing a certain amount of elemental silicon particles and covering the porous carbon precursor, then placing the graphite crucible in a vacuum sintering furnace, evacuating to below 10 Pa, heating to 1550° C. and holding for 0.5 h, then introducing high-purity argon gas and cooling to room temperature with the furnace.

[0068] The open porosity of the porous carbon material obtained in Comparative Example 1 was measured by the Archimedean drainage method to be 45.20%, and the bulk density was 1.000 g / cm 3 Mercury intrusion testing revealed that the pore size of the porous carbon material was primarily concentrated at 3.12 μm. The sample pore size was too small, preventing silicon from fully penetrating the sample during subsequent reaction sintering.

[0069] Comparative Example 2

[0070] The preparation process of the porous carbon material in this comparative example 2 refers to that in Example 1, with the only difference being that in step (3), the particle size of the mixed particles obtained by screening is 100 to 150 μm. The porous carbon material prepared in this comparative example 2 is used as a precursor to prepare a silicon carbide-carbon composite material, comprising the following steps: placing the porous carbon precursor in a graphite crucible coated with boron nitride, weighing a certain amount of elemental silicon particles and covering the porous carbon precursor, then placing the graphite crucible in a vacuum sintering furnace, evacuating to below 10 Pa, heating to 1550° C. and holding for 0.5 h, then introducing high-purity argon gas and cooling to room temperature with the furnace.

[0071] The microstructure of Comparative Example 2 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Comparative Example 2 was measured by the Archimedean drainage method to be 51.16%, and the bulk density was 0.894 g / cm 3 Mercury intrusion testing revealed that the pore sizes of the porous carbon material were primarily concentrated at 1.57 μm and 16.41 μm. The sample's excessive porosity resulted in a high infiltration of molten silicon during subsequent sintering reactions. Furthermore, the particle size was too small, resulting in too little residual carbon remaining after the outer layer of the porous carbon particles reacted with silicon, making it unsuitable for material application.

[0072] Comparative Example 3

[0073] The preparation process of the porous carbon material in this comparative example 3 refers to that in Example 1, with the only difference being that in step (4), the molding pressure is 20 MPa.

[0074] The microstructure of Comparative Example 3 is similar to that of Example 1. The open porosity of the porous carbon material obtained in Comparative Example 3 was measured by the Archimedean drainage method to be 28.63%, and the bulk density was 1.341 g / cm 3 Mercury intrusion testing revealed that the pore sizes of the porous carbon material were primarily concentrated at 1.81 μm and 12.79 μm. Due to the small porosity, silicon could not fully penetrate the sample during subsequent reaction sintering.

[0075] Comparative Example 4

[0076] The preparation process of the porous carbon material in this comparative example 4 refers to that in Example 3, with the only difference being that in step (4), the molding pressure is 2 MPa, and after dry pressing, the material is not placed in an oven for heating but is directly demolded.

[0077] The sample in this comparative example 4 could not be formed.

[0078] Comparative Examples 1-2 and Comparative Examples 1-2 show that as the particle size of the mixed particles increases, the pore size of the porous carbon material shows a monotonically increasing trend. Comparative Example 1, Example 3, Example 4, and Comparative Example 3 show that, when other conditions are the same, as the molding pressure increases, the density of the porous carbon material increases and the porosity decreases. If the molding pressure is too high, the porosity of the porous carbon material will be too small, and the molten silicon will not be able to completely penetrate the sample during the subsequent reaction and sintering process. Comparative Example 1, Example 3, Example 4, and Comparative Example 3 show that the pore size of the pressurized sample decreases compared to the non-pressurized sample, but after pressurization, as the molding pressure increases, the pore size does not change much. Comparative Examples 5-7 show that as the binder ratio increases, the density of the porous carbon precursor decreases and the porosity increases. Comparative Example 4 and Example 8 show that the reduction in the needle coke particle size may cause the density of the porous carbon precursor to decrease and the porosity to increase. Comparative Example 3 and Example 9 show that as the holding time increases, the porosity of the porous carbon precursor can be improved. Comparing Example 1, Example 10, and Example 11, it can be seen that as the softening point of the pitch increases and the volatile matter decreases, the density of the porous carbon precursor increases and the porosity decreases. Carbon reacts violently with molten silicon. Upon contact, it reacts rapidly to form a SiC layer of a certain thickness. Subsequently, due to the obstruction of the SiC layer, the reaction rate slows down. Comparing Example 5 and Comparative Example 2, it can be seen that when the sample is not pressurized during molding, the porosity of the porous carbon material is too large and the particle size of the mixed particles is too small. During the reaction sintering process, after carbon and silicon react to remove a certain thickness, the resulting composite material has a low residual carbon content and cannot meet the application requirements. Increasing the molding pressure can reduce the porosity and reduce the amount of silicon infiltration during the reaction sintering process, thereby increasing the residual C rate of the composite material after reaction sintering.

[0079] Figure 1 The TGA and DSC curves of the porous carbon blank of the present invention show that the sample has large exothermic peaks at around 450°C and 950°C, and the maximum mass loss occurs at around 450°C.

[0080] Figure 2 This is a surface morphology of the porous carbon material prepared in Example 4 of the present invention. As can be seen from the figure, the sample has a porous microstructure.

[0081] Figure 3 The pore size distribution diagram of the porous carbon materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1-2 of the present invention is shown in FIG. As can be seen from the figure, as the particle size of the mixed powder increases, the pore size of the porous carbon material gradually increases.

[0082] Figure 4The pore size distribution diagram of the porous carbon materials prepared in Examples 3-4 and Comparative Example 3 of the present invention is shown in the figure. Figure 2 As can be seen from Example 1 in the figure, after the molding pressure increases, the pore diameter will first decrease, but after pressurization, the pore diameter will remain stable as the pressure increases.

[0083] Figure 5 This is a BSE image of the composite material prepared by sintering the porous carbon blank obtained in Example 4. As can be seen from the figure, the residual carbon content of the composite material is 39 vol.%, and the residual Si content is 8 vol.% (calculated using Image Pro Plus statistical area ratio).

[0084] Figure 6 This is a sample of the porous carbon material obtained after reaction sintering in Comparative Example 1 of the present invention. As can be seen from the figure, due to the small pore size of the porous carbon, the molten silicon cannot completely penetrate the sample during the reaction sintering process, resulting in no reaction in the center of the porous carbon material.

[0085] Figure 7 This is a BSE image of the composite material prepared by sintering the porous carbon material obtained in Comparative Example 2. As can be seen from the image, the composite material has a residual carbon content of only 17 vol.% and a residual Si content of 13 vol.% (calculated using Image Pro Plus statistical area ratio).

[0086] In summary, the present invention provides a simple and efficient method for preparing porous carbon materials. The microstructure of the porous carbon can be controlled by changing the preparation process parameters of the porous carbon material. The obtained porous carbon material is used as a porous carbon precursor for reaction sintering. By regulating the microstructure of the porous carbon, the degree of reaction between carbon and molten silicon can be controlled, thereby achieving the preparation of a silicon carbide-carbon composite material with a high residual carbon content and a low residual Si content. At the same time, the SiC generated in situ during the siliconization process can enhance the bonding strength between carbon and silicon carbide.

Claims

1. A method for preparing a novel porous carbon material, characterized in that: The following steps are involved: (1) placing needle coke and coal tar pitch having a certain softening point in a kneader, heating and stirring the mixture to obtain mixed particles in which the needle coke is coated with molten pitch; (2) crushing and screening the mixed particles obtained in step (1) into a mixed powder of a certain particle size, dry-pressing the mixed powder, and heating the mixed powder in an oven to re-melt and solidify the asphalt to obtain a porous carbon blank; (3) Carbonizing the porous carbon blank obtained in step (2) to obtain the novel porous carbon material.

2. The preparation method according to claim 1, characterized in that The particle size of the needle coke is 15 to 150 μm; The softening point of the coal tar pitch is 45-180° C., preferably 80-115° C.; the volatile matter of the coal tar pitch is ≥50%, preferably 60-75%.

3. The preparation method according to claim 1 or 2, characterized in that The mass ratio of the needle coke to the coal tar pitch is (1-4):1, preferably (1.5-3):

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the heating and stirring mixing method is: first pour the needle coke into a kneader, heat and stir for 30 to 60 minutes, and then add the molten asphalt into the kneader for kneading; wherein the heating and stirring temperature is 150 to 250°C, preferably 170 to 220°C; the kneading time after adding the molten asphalt is 1 to 3 hours, preferably 1.5 to 2 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that In step (2), the particle size of the mixed powder after crushing and screening is ≤250 μm, preferably 100 to 250 μm.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step (2), the dry pressing pressure is 0 to 18 MPa, preferably 8 to 18 MPa.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step (2), the heating temperature is 150-250° C., and the heating time is 0.5-3 h; preferably, the heating temperature is 190-220° C., and the heating time is 1-2 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that In step (3), the parameters of the carbonization treatment include: evacuating to below 10 Pa, heating to 450-600°C at a heating rate of 1-3°C / min and keeping warm for 0-8 hours, then heating to 900-1000°C at a heating rate of 1-3°C / min and keeping warm for 0.5-2 hours, then introducing high-purity argon gas and cooling to room temperature with the furnace.

9. A novel porous carbon material prepared according to the preparation method according to any one of claims 1 to 8.

10. The novel porous carbon material according to claim 9, characterized in that: The novel porous carbon material has an open porosity of 28-53% and a bulk density of 0.884-1.354 g / cm 3 .